Circulative Funds, Loans, Term Deposits And Savings In Gross Domestic Product - Achadyah Prabawati; Siti Husnul Hotima (Institute of Computer Science (IOCS), 2024)
Business activities in a country are greatly influenced by the conditions of that country. In Indonesia, with Covid-19, the amount of public loans for working capital, business and consumption has increased. However, before Covid-19, there was a decline from 2017 to 2020. So, with the decreasing increase in the number of loans, it can be interpreted that community business activities have decreased. With the decline in community businesses, funds for operational business activities are saved. So that deposits and savings will increase from 2017 to 2020. As a result of the decline in business operations in the business world, this will result in a decrease in Gross Domestic Product from 2017 to 2020. However, in reality the funds circulating in society have increased during this time. After the Covid-19 pandemic has passed, circulating funds will decrease again in 2022. Under these conditions, the research aims to determine whether there is a relationship between circulating funds, loans, deposits and savings on Gross Domestic Product in Indonesia.